The Commonwealth Caribbean : the integration experience : report of a mission sent to the Commonwealth Caribbean by the World Bank - Chernick, Sidney E. (J. Hopkins Univ. P. BaltimoreUS, 1978)
Examines the problems and prospects of economic integration among small developing countries. Focuses on a group of twelve Commonwealth Caribbean territories that are in the process of forging and integrated community.